Enhancing Students' Writing Skill through Contextual Teaching and Learning Approach: writing - Jubhari, Yuristson; Sasabone, Luana; Nurliah, Nurliah (International Journal of Language Teaching and Education, 2023)
This study is an endeavor to examine efficacy of using CTL approach in writing class of the senior high-school student. The participants consisted of 52 the eleventh grade students’ natural-science class. The experimental group was taught using CTL approach while the control one taught using conventional one. A writing pre-post test and perceptional questionnaire were the data collection instruments. Finding of the test indicated that the experimental group performed better that of control one in terms of the post-test while the questionnaire indicated that students’ experimental group had positive perception related to the application of the teaching approach.